2005
DOI: 10.1002/gps.1402
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the clinical effectiveness of donepezil, rivastigmine and galantamine on cognition, quality of life and adverse events in Alzheimer's disease

Abstract: The cholinesterase inhibitors donepezil, rivastigmine, and galantamine can delay cognitive impairment in patients with mild to moderately-severe AD for at least 6 months duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
132
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(145 citation statements)
references
References 30 publications
7
132
2
4
Order By: Relevance
“…Both are current therapies for Alzheimer's disease and have been shown to improve cognitive ability in Alzheimer's disease patients (Burns et al, 1999;Winblad et al, 2001Winblad et al, , 2006Peskind et al, 2006;Takeda et al, 2006). In the present study, both of these compounds also increased the distance moved in response to the acoustic stimulus in a similar manner to rolipram.…”
Section: Discussionsupporting
confidence: 67%
“…Both are current therapies for Alzheimer's disease and have been shown to improve cognitive ability in Alzheimer's disease patients (Burns et al, 1999;Winblad et al, 2001Winblad et al, , 2006Peskind et al, 2006;Takeda et al, 2006). In the present study, both of these compounds also increased the distance moved in response to the acoustic stimulus in a similar manner to rolipram.…”
Section: Discussionsupporting
confidence: 67%
“…A systematic review published in early 2006 also concluded that use of ChEIs resulted in statistically significant improvement of ADAS-cog scores, compared with placebo; however, the improvements in QOL measures were mixed, and the impact on QOL could not be assessed with certainty. 37 This review concluded that ChEIs could delay cognitive impairment in mildly to moderately severe AD for at least 6 months and mentioned the limited ability of outcome measures to detect clinically significant change in treated patients. In terms of efficacy, a 2006 Cochrane review stated that, despite the slight variations in modes of action, there was no evidence of any differences among the 3 drugs.…”
Section: Cholinesterase Inhibitorsmentioning
confidence: 99%
“…Det er ikke vist i noen undersøkelser at kolinesterasehemmere, som hindrer nedbrytning av acetylkolin, har en annen effekt hos yngre med Alzheimers demens enn hos eldre (42). Nytten av behandling med kolinesterasehemmere eller N-metyl-D-aspartat (NMDA)-antagonister må vurderes hos hver enkelt pasient.…”
Section: Behandling Forløp Og Prognoseunclassified